2018
DOI: 10.13005/bpj/1528
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Assessment of the Quality of Root Canal Treatments Performed by Practitioners with Different Levels of Experience

Abstract: This retrospective cross-sectional study was conducted to radiographically evaluate the quality of root canal treatment (RCT) performed by practitioners with different levels of experience at the Arar Dental Center, North Region, Saudi Arabia. A total of 170 periapical radiographs of root canal fillings (RCFs) were used to assess the technical quality of 376 root canal performed by the practitioners at Arar Dental Center. The length of each RCF was categorized as acceptable, overfilled, and underfilled on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Results of post and core restorations in the prosthetic treatment plan depend upon the proper diagnosis and treatment planning and each phase of that plan to be delivered perfectly. Hence, the assessment must be performed as follows as before post insertion, checking of root canal treatment (RCT) system seal, after cementation, during follow-up after teeth exposed to masticatory loading forces, and monitoring during maintenance recall to evaluate the treatment method 3,4 . Typically, a correlation exists between preclinical performance on phantom lab on a typhodont and clinical performance on patients which is relevant to the preparation of post and core restorations by dental students 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Results of post and core restorations in the prosthetic treatment plan depend upon the proper diagnosis and treatment planning and each phase of that plan to be delivered perfectly. Hence, the assessment must be performed as follows as before post insertion, checking of root canal treatment (RCT) system seal, after cementation, during follow-up after teeth exposed to masticatory loading forces, and monitoring during maintenance recall to evaluate the treatment method 3,4 . Typically, a correlation exists between preclinical performance on phantom lab on a typhodont and clinical performance on patients which is relevant to the preparation of post and core restorations by dental students 5 .…”
Section: Introductionmentioning
confidence: 99%
“…However, when the endodontic treatment procedures are performed by the differently skilled clinicians, the quality of the endodontic treatment differs significantly [22,23]. Bajawi et al (2018) have found that the quality of root-canal obturation performed by ED was significantly better in comparison to general dental practitioners (GDP) [24]. The same was observed by other investigators, demonstrating better clinical outcomes when endodontic treatment was performed by ED in comparison to GDP [25,26].…”
Section: Introductionmentioning
confidence: 79%